Pengaruh Kadar Asam Stearat,Mercaptodibenzothiazyldisulfide (MBTS) Dan Sulfur Terhadap Sifat Dan Morfologi Thermoset Rubber Dengan Filler Carbon Black-Abu Terbang Sawit - Mery Christina; Bahruddin Bahruddin; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Crude palm oil wastes in the form of fly ash is potentially use as filler for thermoset rubber because it contains silica. This study aims to increase the mechanical and morphological properties of thermoset rubber which filled with mixture of carbon black and fly ash with particles size screened to 700-800nm. Stearic Acid, MBTS and sulfur contents were used 1; 2; 3 phr (per hundred rubber), 0.5; 1; 1.5 phr and 0.5; 1.5; 3 phr respectively. Rubber mastication process performed by a roll mill at room temperature and roll speed of 20 rpm until the texture is smooth and soft, then added minarex as a plasticizer, nanofiller, and other additives, such as ZnO as an activator, stearic acid as a co-activator, as antidegradant TMQ, MBTS as an accelerator and sulfur as a curative agent. Rubber mastication performed by a roll mill at room temperature and roll speed of 20 rpm. The overall duration of the manufacture of compound ±45 minutes. Vulcanization process using a hot press at a pressure of 200 kgf/cm2 and a temperature of 150 oC. Results showed that increased levels of stearic acid, MBTS and sulfur is directly proportional to the tensile strength, but yield elongation at break are varied. The best thermoset rubber in this study were obtained on samples having content of stearic acid 3 phr, MBTS 1.5 phr and sulfur 3 phr with tensile strength values 19,05 MPa, 774.394 % elongation at break, hardness 52±5 shore A, abration 0,074 mm3/kg and 1,28% water absorption percentage. Keywords: carbon black, natural rubber, palm oil mill fly ash, vulcanizate